GREEN INFORMATION TECHNOLOGIES: DEVELOPMENT OF RECYCLING AND RESOURCE-EFFICIENT INFORMATION PLATFORMS - Farrukh Murodov (The Conference Hub, 2025)
This in the article green information technologies content , their ecological and economic importance, electronic waste again performance, energy efficiency increase and resource economical platforms develop issues illuminated. The work purpose cloudy computing, virtualization and energy saver of equipment importance and to the environment negative the effect to reduce aimed at measures analysis from doing consists of.
Keywords: green technologies, information systems, environmental security, electronic waste, recycling performance, energy efficiency, cloudy computing, virtualization, resource thrift, digital infrastructure.